2006
DOI: 10.1111/j.1365-2982.2006.00881.x
|View full text |Cite
|
Sign up to set email alerts
|

The peptide hormone xenin induces gallbladder contractions in conscious dogs

Abstract: Xenin is a 25-amino acid peptide isolated from human gastric mucosa. The biological activities of xenin include modulating intestinal motility and affecting exocrine pancreatic secretion and gastric acid secretion. The physiological effect of xenin on the gastrointestinal tract, however, is incomplete. The objective of this study is to investigate the effects of xenin on the gastrointestinal tract motility of conscious dogs. Gastrointestinal tract and gallbladder contractions were monitored by chronically impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…Thus effects of Xen on insulin release may be independent of the central nervous system. Consistent with this hypothesis, effects of Xen on gall bladder contractions are inhibited by atropine, but not vagotomy (23).…”
mentioning
confidence: 74%
See 2 more Smart Citations
“…Thus effects of Xen on insulin release may be independent of the central nervous system. Consistent with this hypothesis, effects of Xen on gall bladder contractions are inhibited by atropine, but not vagotomy (23).…”
mentioning
confidence: 74%
“…In animals, Xen delays gastric emptying (25), reduces food intake (2,10,27), increases gut motility (17), augments gall bladder contractions (23), and enhances secretion from the exocrine pancreas (16). Many of these Xen effects are known to be mediated by neurons (9,10,23,25,27). In vivo mouse studies from our (54) and another (30) laboratory demonstrated that Xen increases the effects of GIP on insulin release.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Early studies identified a contraction and relaxation effect of xenin in the jejunum, and a relaxation effect in the colon of guinea pigs . Subsequent studies have shown xenin to elicit dose-dependent contractions in dog gall bladder and non-dose-dependent contractions in the jejunum (Kamiyama et al 2007). …”
Section: Introductionmentioning
confidence: 99%
“…The fact that GHRP-2 inhibited postprandial upper gastrointestinal contractions in dogs with vagotomy without increasing food intake suggests that the motor inhibitory effect of GHRP-2 on the upper gastrointestinal tract is not linked to food intake. We did not verify the completeness of vagotomy, because surgical abdominal vagotomy is a very well established method and often performed in dogs to study the role of the vagal nerve [29,30]. When antagonists are used to see if they reverse the effect induced by an agent, it is important to confirm that administration of those antagonists did not alter basal motor activity.…”
Section: Discussionmentioning
confidence: 98%